IMPLEMENTASI KEBIJAKAN KETERBUKAAN INFORMASI PUBLIK DI BIDANG HUBUNGAN MASYARAKAT (HUMAS) KEPOLISIAN DAERAH (POLDA) SULTENG - Sumandjaya, Agung (Katalogis, 2016)
This study aimed to describe the implementation practice of public disclosure policy at Central Sulawesi Police. This study used qualitative research method. Informants in this study were Head of Public Relations Unit of Central Sulawesi Police, the people, and the media. Data collection techniques in this study were observations, interviews, and documentations. The result shows that the implementation of public disclosure policy at Public Relations Unit of Central Sulawesi Police had not been going well, seen from the public implementation indicators of Edward III. The Communication aspect had not worked, in which not all work units had been providing information to the information and documentation management officers (pejabat pengelola informasi dan dokumentasi – PPID) as well as people had not yet known that Central Sulawesi Police had been implementing public disclosure policy. Similarly, the aspect of Resources to implement this policy had many limitations. There were 24 personnels at the Public Relations Unit, none of which had the educational qualification of Communication. The aspect of Bureaucracy Structure had still not supporting also. It can be seen from the structure of the PPID which had no patron to assert its position to the Work Units of Central Sulawesi Police, which had some of the PPID’s functions.